From Sensing to Reconfiguring: A Theoretical Framework of Dynamic Capabilities in Social Media Marketing Strategy - Santos, Clara; Herrera, Miguel; Rivera, Bianca (ICON Publisher, 2025)
This conceptual paper develops an integrative framework linking Dynamic Capabilities Theory (DCT) to social media marketing strategy. In increasingly volatile digital environments, firms must move beyond platform presence toward the strategic orchestration of sensing, seizing, and reconfiguring capabilities. Drawing on existing literature in strategic management and digital marketing, the study reconceptualizes social media not merely as a communication channel but as an ecosystem for continuous adaptation and strategic renewal. Sensing is defined as real-time consumer insight generation, seizing as opportunity activation through agile campaign execution, and reconfiguring as the structural adjustment of digital strategies and teams. The proposed model highlights the recursive nature of these capabilities and identifies key organizational enablers such as cultural agility and digital leadership. The paper contributes to both theory and practice by offering a strategic lens for understanding how marketing agility is achieved in fast-changing online environments. It also provides theoretical propositions and future research directions to guide empirical validation and model refinement.